2023
DOI: 10.1186/s13054-023-04558-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative inspired oxygen fraction (FiO2 0.3 vs 0.8) on patients undergoing off-pump coronary artery bypass grafting: the CARROT multicenter, cluster-randomized trial

Abstract: Background To maintain adequate oxygenation is of utmost importance in intraoperative care. However, clinical evidence supporting specific oxygen levels in distinct surgical settings is lacking. This study aimed to compare the effects of 30% and 80% oxygen in off-pump coronary artery bypass grafting (OPCAB). Methods This multicenter trial was conducted in three tertiary hospitals from August 2019 to August 2021. Patients undergoing OPCAB were clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Furthermore, hyperoxia treatment was more moderate, with a mean PaO 2 of 178 mm Hg during CPB compared to 377 mm Hg in the current study. More recently, Nam and colleagues, 37 found in a cluster crossover trial that 0.8 FiO 2 during off-pump coronary artery bypass grafting surgery did not affect hospital length of stay vs 0.3 FiO 2 but did result in a 50% decrease in AKI. In addition, Shaefi et al 38 and Holse et al 39 reported results of randomized oxygen treatment trials targeting cognitive function and myocardial injury, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hyperoxia treatment was more moderate, with a mean PaO 2 of 178 mm Hg during CPB compared to 377 mm Hg in the current study. More recently, Nam and colleagues, 37 found in a cluster crossover trial that 0.8 FiO 2 during off-pump coronary artery bypass grafting surgery did not affect hospital length of stay vs 0.3 FiO 2 but did result in a 50% decrease in AKI. In addition, Shaefi et al 38 and Holse et al 39 reported results of randomized oxygen treatment trials targeting cognitive function and myocardial injury, respectively.…”
Section: Discussionmentioning
confidence: 99%